PENGARUH KEPUASAN KERJA,MOTIVASI DAN KOMITMEN ORGANISASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Fitriani, Vina; Atmadjaya, Yovita V. I.; Nilawati, Wardha (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
This study aims to analyze the effect of job satisfaction, motivation and organizational commitment on organizational citizenship behavior of teachers (Non PNS) SMKN 1 Banyuwangi. This type of quantitative descriptive research with explanatory research design. The number of respondents in this study were 35 teachers. Sampling technique Nonprobability sampling, Saturated Sampling sampling method. Data collection techniques using observation, interviews and questionnaires. Data analysis techniques used instrument testing, classical assumption testing, multiple linear regression analysis, hypothesis testing and the coefficient of determination. The data processing tool uses SPSS Version 25 software. he results of this study indicate that the variables of job satisfaction and organizational commitment have a positive and significant effect on organizational citizenship behavior while motivation has no effect on organizational citizenship behavior. Evidenced by the calculated F value of 28.972 greater than the F table of 2.911, the t count for job satisfaction is 3.569 greater than the t table of 1.695 with a significant (0.01 <0.05), so that Ho is rejected and H1 is accepted, The calculated t for motivation of -0.801 is greater than the t table of -1.695 significantly (0.429 > 0.05), so Ho is rejected and H2 is accepted, and the calculated t for organizational commitment of 6.318 is significantly greater than the t table of 1.695 ( 0.00 < 0.05) so that Ho is rejected and H3 is accepted